Question

1.1 .4 1.1 .5 Solve for \( x \) and \( y \) simultaneously \( 38-y+2=0 \) and \( y=-x^{2} + 2 x=12 \)

Ask by Hill Wyatt. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

There are no real solutions for \( x \) and \( y \) in the given system of equations.

Solution

Solve the system of equations \( 38-y+2=0;y=-x^{2}+2x-12 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}38-y+2=0\\y=-x^{2}+2x-12\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}40-y=0\\y=-x^{2}+2x-12\end{array}\right.\) - step2: Solve the equation: \(\left\{ \begin{array}{l}y=40\\y=-x^{2}+2x-12\end{array}\right.\) - step3: Substitute the value of \(y:\) \(40=-x^{2}+2x-12\) - step4: Swap the sides: \(-x^{2}+2x-12=40\) - step5: Move the expression to the left side: \(-x^{2}+2x-12-40=0\) - step6: Subtract the numbers: \(-x^{2}+2x-52=0\) - step7: Multiply both sides: \(x^{2}-2x+52=0\) - step8: Solve using the quadratic formula: \(x=\frac{2\pm \sqrt{\left(-2\right)^{2}-4\times 52}}{2}\) - step9: Simplify the expression: \(x=\frac{2\pm \sqrt{-204}}{2}\) - step10: The expression is undefined: \(x \notin \mathbb{R}\) - step11: The system of equations has no solution in the set of real numbers: \(\left(x,y\right) \notin \mathbb{R}^{2}\) - step12: Alternative Form: \(\textrm{No real solution}\) The system of equations \(38-y+2=0\) and \(y=-x^{2}+2x-12\) does not have any real solutions.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equations \( 38 - y + 2 = 0 \) and \( y = -x^2 + 2x = 12 \) simultaneously, we start with the first equation. Rearranging the first equation gives: \[ y = 40 \] Next, we substitute this value of \( y \) into the second equation. However, there seems to be a mistake in the presentation of the second equation as it appears to combine two expressions. It likely means \( y = -x^2 + 2x \) and subsequently equate it to 12. Let's first clarify the second expression: 1. Set \( y = -x^2 + 2x \) and then combine it with \( 40 = -x^2 + 2x \). This gives us the equation: \[ 40 = -x^2 + 2x \] Rearranging this leads to: \[ x^2 - 2x + 40 = 0 \] Next, we can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) where \( a = 1, b = -2, c = 40 \): \[ x = \frac{2 \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 40}}{2 \cdot 1} \] \[ x = \frac{2 \pm \sqrt{4 - 160}}{2} \] \[ x = \frac{2 \pm \sqrt{-156}}{2} \] \[ x = \frac{2 \pm 2i\sqrt{39}}{2} \] \[ x = 1 \pm i\sqrt{39} \] Now, substituting these \( x \) values back into \( y = 40 \) gives us: - For \( x = 1 + i\sqrt{39} \), \( y = 40 \) - For \( x = 1 - i\sqrt{39} \), \( y = 40 \) So, our solutions are: 1. \( (1 + i\sqrt{39}, 40) \) 2. \( (1 - i\sqrt{39}, 40) \) Enjoy these complex solutions which show that mathematics can get a little wild!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy